The Relationship Between Company Compliance Levels with Occupational Health and Safety (K3) Claims in the Manufacturing Sector: A Literature Review (Maneggio, 2026)
This study aims to examine the relationship between corporate compliance with Occupational Safety and Health (OSH) standards and the high number of Work Accident Insurance (JKK) claims in the manufacturing sector. The background of the study is based on the high number of occupational accident cases in Indonesia, which reached 462,241 cases in December 2024, with the highest concentrations in industrial regions such as East Java and West Java. This research employs normative legal research and literature review methods using statutory, conceptual, and case approaches. The data were obtained from primary and secondary legal materials as well as occupational accident statistics as supporting data. The findings show that low levels of compliance with OSH standards have a significant correlation with the increase in JKK claims. The effectiveness of OSH implementation is influenced by management commitment, quality of OSH management systems, safety culture, worker competence, and the effectiveness of supervision and law enforcement. This study concludes that strengthening substantive compliance with OSH standards is a key factor in reducing the number of JKK claims in the manufacturing sector in Indonesia.